Venous thromboembolism incidence, recurrence, and mortality based on Women's Health Initiative data and Medicare claims. Issue 150 (February 2017) - Burwen, Dale R.; Wu, Chunyuan; Cirillo, Dominic; Rossouw, Jacques E.; Margolis, Karen L.; Limacher, Marian; Wallace, Robert; Allison, Matthew; Eaton, Charles B.; Safford, Monika; Freiberg, Matthew
Abstract: Introduction: Our objective was to compare Medicare claims to physician review and adjudication of medical records for identifying venous thromboembolism (VTE), and to assess VTE incidence, recurrence, and mortality in a large national cohort of post-menopausal women followed up to 19 years. Materials and methods: We used detailed clinical data from the Women's Health Initiative (WHI) linked to Medicare claims. Agreement between data sources was evaluated among 16, 003 women during 1993–2010. A claims-based definition was selected to analyze VTE occurrence and impact among 71, 267 women during 1993–2012. Results: Our VTE definition had 83% sensitivity. Positive predictive value was 69% when all records were included, and 94% after limiting Medicare records to those with a WHI hospitalization adjudicated. Annualized VTE incidence was 4.06/1000 person-years (PY), recurrence was 5.30/100 PY, and both rates varied by race/ethnicity. Post-VTE mortality within 1 year was 22.49% from all causes, including 1.01% from pulmonary embolism, 10.40% from cancer, and 11.08% from other causes. Cancer-related VTE compared to non-cancer VTE had significantly (p < 0.001) higher recurrence (9.86/100 PY vs. 4.43/100 PY) and mortality from all causes (45.89% vs. 12.28%), but not from pulmonary embolism (0.40% vs. 1.27%). Conclusions: Medicare claims compared reasonably well to physician adjudication. The combined data sources provided new insights about VTE burden and prognosis in older women. Highlights: Medicare claims compared reasonably well to medical record adjudication for VTE. In a national cohort of older women, VTE incidence varied by race/ethnicity. Incidence was highest in African-Americans and lowest in Asians/Pacific Islanders. VTE recurrence and all-cause mortality were high, especially in women with cancer. High post-VTE mortality in cancer patients appears due to cancer rather than VTE.